Literasi Media Mahasiswa Ilmu Komunikasi UPS Tegal Mengenai Hoax Virus Covid-19 Di Social Networking Berdasarkan ICF - Ma’rifatul Aeni; Ike Desi Florina; Inas Sany Muyassaroh (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
The Internet, as a digital medium, has brought about various conveniences over time. Social media platforms like Facebook and Twitter are commonly utilized for information seeking and sharing. Among the information disseminated on social media is the increasingly prevalent Covid-19 information from 2019 to 2021. Irresponsible individuals spread hoax information, leading audiences to trust such misinformation. Therefore, Communication Science students, who will enter the media realm, require proficient media literacy skills. This research employs descriptive methods to comprehend occurring phenomena, utilizing purposive sampling for informant selection. The study includes 184 respondents from the 2016-2019 student cohorts. Descriptive qualitative analysis, complemented by scale range conversion, is used to transform qualitative data into quantitative format. The research aims to assess Communication Science students' media literacy skills through the Individual Competence Framework, comprising technical skills, critical understanding, and communicative abilities. Findings indicate students' proficient use of computers and the Internet. While they comprehend social media content and functions well, improvements are needed in behavior and regulation. Additionally, enhancing communication and relationship-building skills on social networking sites, as well as community participation and content production through these platforms, is imperative, suggesting the necessity for further development.